Analyze of the difference of wastage level between residential and commercial buiding using prefabrication method - Mimi Syafizah, Yusof (2011)
The construction industry consumes huge amounts of natural resources. The current implementation of prefabrication seems unable to provide satisfactory result to the construction industry. This paper provides partly an initial study, to identify types of construction solid waste on site, to identify the causes of construction waste and to examine the wastage level in adopting prefabrication in construction activities between two (2) types of building which are residential and commercial building. Generation of construction wastes constitutes a major impact to the environment. The awareness among contractors and builders regarding waste minimization is still low although various researchers have proved that environment of problems are getting more critical. Construction cost and technology are the important parameters that determine the material wastage. The data were obtained from 16 and 14 respondents on residential and commercial respectively through questionnaires that have been distributed at Selangor, Kuala Lumpur and Pahang area. All the data have been analyzed using average index. Site observation has been carried out to get additional information. All of the respondents are site engineers, contractors and manufacturers of Industrialized Building System. Average Index method will be used to analyze the data obtained. As a conclusion, types of construction waste such as concrete and timber, causes of construction waste such as careless at design stage and lack of communication between leader and worker and the difference of wastage level between residential and commercial building using fabrication method are established. In commercial building, the most average wastage is timber with value of 8.21. In residential building, the most average wastage in residential is concrete with the value of 11.4. It has been found out that the wastage level in commercial building is lower than residential building.